PENGARUH PENDEKATAN MODEL-ELICITING ACTIVITIES TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIK SISWA SMP NEGERI DI KOTA CIMAHI - Siti Chotimah; Fathoni Akhmad Ramdhani; Martin Bernard; Padillah Akbar (Departement of Mathematics Education, 2019)
This research is motivated by the still low level of mathematical critical thinking skills of State Middle School students in Cimahi City, so a learning approach is needed to overcome these problems. Alternative approaches are applied, namely the approach to Model-Eliciting Activities. This study aims to examine the mathematical critical thinking skills of State Middle School students in Cimahi City. The method used in this study is an experimental method with research in the form of a pretest-posttest Control Group Design. The population in this study were all public junior high schools in the city of Cimahi randomly selected and selected SMP Negeri 10 Cimahi representing the characteristics of the population. The sample was chosen by two classes in a random class, namely the experimental class and the control class. Data collection in this study used a descriptive test, then the score data of the students' mathematical critical thinking skills were analyzed by descriptive and inferential statistics using the two average difference test. Based on the results of the study, both from the results of data analysis and hypothesis testing, it can be concluded that the mathematical critical thinking skills of the State Middle School students in Cimahi City whose learning using the MEAs approach are better than those using conventional learning.